2009
DOI: 10.1016/s1734-1140(09)70088-x
|View full text |Cite
|
Sign up to set email alerts
|

Blocking angiogenesis with peptides that inhibit the activity of procollagen C-endopeptidase

Abstract: Procollagen C-endopeptidase (BMP-1) is one of two key enzymes crucial for conversion of fibrillar procollagens to self-assembling collagen monomers. Recently, we have reported inhibition of the largest variant of BMP-1, a recombinant mammalian tolloid (mTld) in vitro, on procollagen type I using peptides with amino acid sequences in chordin conserved across different species. Here, we tested the same peptides as potent blockers of angiogenesis ex vivo in cultured rings of rat aorta, in vivo in chick embryos, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…B/TP cleavage of perlecan liberates the anti-angiogenic fragment endorepellin (67). However, peptides that inhibit mTLD in vitro may reduce angiogenesis in some systems (69). Thus, B/TPs may balance regulation of angiogenesis by assisting in blood vessel growth while releasing anti-angiogenic factors to prevent excessive angiogenesis.…”
Section: Non-collagenous Ecm-related Proteinsmentioning
confidence: 99%
“…B/TP cleavage of perlecan liberates the anti-angiogenic fragment endorepellin (67). However, peptides that inhibit mTLD in vitro may reduce angiogenesis in some systems (69). Thus, B/TPs may balance regulation of angiogenesis by assisting in blood vessel growth while releasing anti-angiogenic factors to prevent excessive angiogenesis.…”
Section: Non-collagenous Ecm-related Proteinsmentioning
confidence: 99%
“…However, blocking their activities inhibited the growth of blood vessels in chick embryos. In vitro studies have shown that this is due to the reduction in the rate of endothelial cell proliferation [62].…”
Section: Discussionmentioning
confidence: 99%
“…Their action is critical for the production of collagen fibrils in connective tissue. In aortal walls, the lack of their activity leads to weaker wall structure, possible development of aneurysm and its rupture, among other general tissue problems [ 23 , 24 , 25 ]. Genetic, inherited diseases manifested by the development of aneurysms are some cases of progressively deforming type 3 osteogenesis imperfecta (OI) with a mutation in the gene encoding BMP1, [ 26 ] also classified as OI type XIII [ 27 ], dermatosparaxis with mutations in ADAMTS-2 [ 28 ], and mutations in COL3A1, causing the vascular type of Ehlers–Danlos Syndrome [ 29 ].…”
Section: The Aortic Wall Structurementioning
confidence: 99%
“…They are classified to six different families, depending on the specific substrate of the ECM component [ 34 , 35 ]. On the basis of the substrates and the organization of the domains of metalloproteinases, the following families of these enzymes have been proposed: collagenases, gelatinases, stromelysins, matrilysins, metalloelastase, and membrane-type (MT) MMPs ( Table 2 ) [ 4 , 23 , 24 ].…”
Section: The Aortic Wall Structurementioning
confidence: 99%